Analisis Stres Finansial Dalam Perspektif Gender Pasca Konflik - Marselinda Agustin Hege; Petrisia Anas Waluwandja (Universitas Islam Kadiri, 2019)
This research aimed to investigate the financial stress difference from Universitas Persatuan Guru 1945 NTT in the gender perspective. This research is explanation research by using independent sample t-test analysis technique. The population in this study amounted to 66 respondents, consisting of 6 permanent lecturers from 11 courses at Universitas Persatuan Guru 1945 NTT, while the sample selection technique used in this study was saturation sampling. Data collected using the Financial Stress Questionnaire. The results showed that there was a significant difference between the male and female lecturers' financial stress (0,004<0.05), where the mean showed the female lecturers (85.1212) had higher financial stress than Male lecturers (79.1515).